Redefining CRM for the Digital Age: The Role of Customer Data Protection from an Islamic Perspective - Furwanti, Reni; Casmini, Casmini; Wibowo, Muhammad Ghafur (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
ABSTRACT - This study refines Customer Relationship Management (CRM) as a strategic approach for the digital era. It proposes Customer Data Protection (CDP) as a crucial new dimension for a more holistic CRM framework. This revised framework addresses inconsistencies in past CRM definitions, which have contributed to implementation failures across industries. The urgency for this refinement is further emphasized by Indonesia's weak data security landscape. Employing a quantitative survey methodology, the study gathers data from 412 respondents selected through purposive sampling. Confirmatory Factor Analysis (CFA) is then utilized to analyze each CRM dimension within the collected data. The empirical findings establish five significant dimensions of CRM, forming a strategic framework referred to as the